Radiotherapy and olaparib in combination for carcinoma of the oesophagus: A phase I study. (May 2023) - Sheikh, Hamid; Ryder, David; Bateman, Andrew; Chalmers, Anthony; Jackson, Andrew
Highlights: Radiotherapy at a dose of 50 Gy to the thorax with olaparib 50 mg bd may be tolerable. Radiotherapy at a dose of 50 Gy to the thorax with olaparib 100 mg bd results in excessive toxicity. This is the first published trial of radiotherapy plus olaparib for oesophagus cancer. Abstract: Background and purpose: Radical concurrent chemoradiotherapy (CRT) for oesophageal cancer is associated with significant morbidity and is unsuitable for some patients. Olaparib, an inhibitor of the DNA repair enzyme poly-(ADP)-ribose polymerase (PARP) has radiosensitising properties and may be better tolerated than chemotherapy. Materials and methods: We performed a phase 1 study of olaparib with radiotherapy (RT) in oesophageal cancer patients unsuitable for conventional CRT to determine its maximum tolerated dose (MTD) in this setting. Results: Eight patients were recruited. One of 5 patients receiving olaparib 50 mg twice daily and two of 3 receiving 100 mg twice daily experienced dose limiting toxicity (DLT). Conclusions: Olaparib 100 mg twice daily exceeded the MTD in combination with RT in these patients. 50 mg twice daily may be the MTD but this cannot be stated with certainty as the study closed before full recruitment.